The etiological relationship between the general factors of psychopathology and personality; a longitudinal twin study from adolescence into young adulthood - Waaktaar, Trine; Skaug, Eirunn; Torgersen, Svenn (Frontiers in Psychology, 2025)
BackgroundMental disorders and normal personality are interconnected domains. Recent studies highlight the dimensional and hierarchical nature of psychopathology and personality, focusing on their general factor levels. However, their relationship remains unclear.AimsThis study explored the etiological relationship between the general factors of psychopathology and personality from adolescence to young adulthood.MethodsLongitudinal data from seven national twin cohorts (N = 1,538 pairs) were collected across three waves (ages 12–22). Data was analyzed using a genetically informative random intercept cross-lagged panel model and Cholesky decomposition modeling.ResultsNegligible cross-lagged effects were observed between the general factors. Both showed substantial stability, with genetic influences explaining most of the time-invariant variance. About one-quarter of genetic stability was shared.ConclusionPsychopathology and personality are distinct yet parallel domains developing through adolescence into young adulthood. Notably, change in one did not lead to change in the other.